2014
DOI: 10.1016/j.jpainsymman.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine for the Prevention of Chemotherapy-Induced Nausea and Vomiting in Patients Receiving Highly or Moderately Emetogenic Chemotherapy: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: The addition of 5mg/day of oral olanzapine to standard therapy can reduce the frequency of CINV and improve QOL of patients receiving highly or moderately emetogenic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
116
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 28 publications
3
116
0
2
Order By: Relevance
“…19,20 These trials showed that when olanzapine was added to guidelinedirected prophylactic agents, nausea and emesis were significantly reduced. The efficacy of olanzapine for nausea control contrasts with the findings in clinical trials of NK 1 -receptor antagonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 These trials showed that when olanzapine was added to guidelinedirected prophylactic agents, nausea and emesis were significantly reduced. The efficacy of olanzapine for nausea control contrasts with the findings in clinical trials of NK 1 -receptor antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…18 Additional single-institution phase 3 studies have shown that olanzapine combined with standard antiemetic agents improves control of nausea and vomiting in patients receiving moderately or highly emetogenic chemotherapy. 19,20 A recent review, however, pointed to possible methodologic issues in these single-institution studies and called for well-planned, randomized, double-blind, multicenter studies to evaluate the role of olanzapine in the prevention of chemotherapy-induced nausea and vomiting. 21 The primary objective of the current trial was to evaluate olanzapine, as compared with placebo, for the control of nausea in patients receiving highly emetogenic chemotherapy, with nausea prevention assessed during three periods: 0 to 24 hours, 25 to 120 hours, and 0 to 120 hours after chemotherapy.…”
mentioning
confidence: 99%
“…Olanzapine improved the CR and nausea of the delayed period and overall period CINV and the quality of life in patients. In another trial, this one having a randomized, double-blind, placebo-controlled design, 20 44 patients scheduled to receive MEC or HEC received a 5-HT3 receptor antagonist, dexamethasone and a NK-1 receptor antagonist. Patients were then randomized to receive 5 mg of olanzapine daily or placebo for 6 days beginning on the day before chemotherapy or placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Often, the cancer patients have some symptoms of depression and anxiety, and olanzapine can also exert an antidepressant effect in these patients [13,14]. Although there are studies [15][16][17][18][19][20] describing the use of olanzapine for prevention of CINV, there is scarcity of data on Indian patients. Hence, our study was undertaken to compare the effectiveness of olanzapine containing antiemetic regimens with standard regimensJames et al…”
Section: Introductionmentioning
confidence: 99%